Biomechanical analysis of polyaxial locking vs. non-locking plate fixation of unstable fractures of the distal fibula: A cadaver study with a bone only model. Issue 4 (August 2018) - Hallbauer, J.; Gräfenstein, A.; Rausch, S.; Knobe, M.; Simons, P.; Mückley, T.; Hofmann, G.O.; Klos, K.
Highlights: There is no evidence in the literature about plating techniques for surgical management of unstable distal fibula fractures. Up to now specific investigations of comminuted distal fibula fractures are rare. The biomechanical properties of different plate osetosynthesis using a comminuted distal fibula fracture model were compared. Abstract: Background: Open reduction and internal fixation is the current standard of treatment of displaced distal fibula fractures, whereupon using a lag screw often is impossible because of a multifragmantary fracturezone. This study investigates in what extend polyaxial-locking plating is superior to non-locking constructs in unstable distal fibula fractures. Methods: Seven pairs of human cadaver fibulae were double osteotomized in standardized fashion with a 5 mm gap. This gap simulated an area of comminution, where both main fragments were no longer in direct contact. One fibula of the pair was managed using a 3.5-mm screw in a polyaxial-locking construct and the other fibula in a non-locking construct.